儒家和諧文化與新冠疫情應對: Confucian Culture of Harmony and Its Role in Combating the Coronavirus Pandemic - WANG, Jue (International Journal of Chinese & Comparative Philosophy of Medicine, 2020)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. This paper addresses the relationship between politics and ethics from the perspective of the Confucian culture of harmony and argues that it is untenable to ignore the supporting role of Chinese ethical values by attributing China’s achievements in fighting the epidemic to merely the capacities of governance. What the world might learn from China in combating COVID-19 is not only the so-called “national capacity,” nor the theme of trust, but also some deeper moral insights, such as how to cultivate a sense of mutual responsibility in people and regions around the world. These insights have proven to be important ethical resources that human society urgently needs in the post-epidemic era. DOWNLOAD HISTORY | This article has been downloaded 5 times in Digital Commons before migrating into this platform.